Repentance and Compassion in 4Q400–405 Songs of the Sabbath Sacrifice. Are the Deputy Princes in Song Eight Angelic or Human Beings? General Articles - Evans, Annette (Journal for Semitics, 2023)
The pervasive ambiguity in 4QSongs of the Sabbath Sacrifice (SOSS) presents a major problem: When are the activities described in this text performed by angels and when by humans? This paper builds on research on Songs One, Seven, Twelve, Thirteen, and Knowledge in SOSS that hypothesised that as the liturgy proceeds through the thirteen songs of SOSS a gradual transition takes place in the human participants. In Song Six, seven chief princes initially bless God and then proceed to bless various other participants in the liturgy, concluding with “those who wait for Him … for a return of His gracious compassion.” Song Seven, in the middle of the liturgy, describes angelic messenger activity arising from the throne of God, based on Ezekiel’s merkebah chapters. After Song Seven, a dramatic change takes place. In Song Eight, those who do the blessing are no longer “chief” princes, but “deputy” princes. The hypothesis of this article is that these deputy princes are the “people of discernment” introduced in Song One, who, having expressed repentance and persevered in joint exaltation of God with the “holiest of holy ones,” have been transformed into “god-like” messengers of God, to convey God’s compassion to those “who wait for Him.” This paper refers to recent cognitive neuroscience insights in order to, to some extent, support Fletcher-Louis’s proposal of a fluid identity achieved by the participants in the liturgy as a “community of human priests as God’s angels.” In its focus on repentance, compassion, and messenger activity, SOSS may be a witness to the beginnings of a new way of achieving atonement.